Peer Influence Via Instagram: Effects on Brain and Behavior in Adolescence and Young Adulthood. Issue 1 (14th June 2017) - Sherman, Lauren E.; Greenfield, Patricia M.; Hernandez, Leanna M.; Dapretto, Mirella
Abstract : Mobile social media often feature the ability to "Like" content posted by others. This study examined the effect of Likes on youths' neural and behavioral responses to photographs. High school and college students ( N = 61, ages 13–21) viewed theirs and others' Instagram photographs while undergoing functional Magnetic Resonance Imaging (fMRI). Participants more often Liked photographs that appeared to have received many (vs. few) Likes. Popular photographs elicited greater activity in multiple brain regions, including the nucleus accumbens (NAcc), a hub of the brain's reward circuitry. NAcc responsivity increased with age for high school but not college students. When viewing images depicting risk‐taking (vs. nonrisky photographs), high school students, but not college students, showed decreased activation of neural regions implicated in cognitive control. Abstract : The title for this Special Section isContemporary Mobile Technology and Child and Adolescent Development, edited by Zheng Yan and Lennart Hardell